2021
DOI: 10.1002/bse.2925
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing or counterproductive behaviors for sustainable entrepreneurship? The influence of causation and effectuation on sustainability orientation

Abstract: Effectuation, as an emerging theoretical approach in entrepreneurship, is receiving increasing attention in research and practice. Still, the integration of effectuation in sustainable entrepreneurship literature is sparse, and its influence on the sustainability orientation of ventures has so far not been examined in the academic literature. This article, therefore, investigates the influence that causal and effectual behaviors have on the sustainability orientation of established entrepreneurial ventures. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…This means the personal identity of a female entrepreneur influences their sustainability choices and connection to climate change initiatives. Thus, the findings align with the work of Johnson and Hörisch (2022) who in a survey of 140 sustainable ventures found that flexibility of goals influences sustainability orientation. Our findings suggest that gender influences the propensity of women entrepreneurs to engage in climate change issues.…”
Section: Discussionsupporting
confidence: 89%
“…This means the personal identity of a female entrepreneur influences their sustainability choices and connection to climate change initiatives. Thus, the findings align with the work of Johnson and Hörisch (2022) who in a survey of 140 sustainable ventures found that flexibility of goals influences sustainability orientation. Our findings suggest that gender influences the propensity of women entrepreneurs to engage in climate change issues.…”
Section: Discussionsupporting
confidence: 89%
“…I believe the views of Industry expert motivated me to seriously consider entrepreneurship career. Perceived social support Johnson and Hörisch (2021) I believe that the social norms and culture of my community encourages sustainable behaviors. I believe that the social norms and culture of my community emphasizes the responsibility that the venture has in contributing to address community issues.…”
Section: Discussionmentioning
confidence: 99%
“…Further, to assess the triggers derived from the EEP, we used the Souitaris et al (2007) scale, measuring: ‘views of a professor’, ‘views of an external speaker’, ‘views of a visiting entrepreneur’, ‘preparation of a business plan competition’, and ‘views of an industry expert’ on a 5-point scale. Johnson and Hörisch (2021) 4-item scale was employed to measure ‘perceived social support’. All the above constructs were measured on a 5-point Likert scale, 1 = ‘strongly disagree’ and 5 = ‘strongly agree’ (Annexure1).…”
Section: Methodsmentioning
confidence: 99%
“…One of those is the idea that sustainable entrepreneurship while seeking entrepreneurial opportunities which result in economic, social, environmental and ecological wellbeing shapes and reforms existing economic and social structures which result in an institutional change through transforming market structures, sectors, business processes, methods of production, methods of organizing business processes, products, goods and services that lead to sustainable outcomes (Dean & McMullen, 2007; Hockerts & Wüstenhagen, 2010; Patzelt & Shepherd, 2011; Schaltegger & Wagner, 2011; Shepherd & Patzelt, 2011). Furthermore, the complexity of transforming established market structures and market conditions, including considering new market products and services, requires the creation of opportunities under an effectuation logic which goes beyond merely identifying and/or discovering entrepreneurial opportunities (Hall et al, 2010; Hummels & Argyrou, 2021; Johnson & Hörisch, 2021; Sarasvathy, 2001; Sarasvathy & Ramesh, 2019). Effectual entrepreneurial behaviours differ from causal entrepreneurial behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Effectual entrepreneurial behaviours differ from causal entrepreneurial behaviours. The latter aim particularly to identify, recognize and exploit pre‐existing opportunities based on predictable market conditions (Johnson & Hörisch, 2021), whereas the former require the use of entrepreneurial skill, knowledge and network to generate opportunities and develop agility in uncertain and transforming environments and market conditions (Johnson & Hörisch, 2021; Sarasvathy & Ramesh, 2019). However, the extant scholarly definitions do not highlight and/or reflect on the effectual logic under which sustainable entrepreneurs operate to successfully transform market conditions as agents of institutional change.…”
Section: Introductionmentioning
confidence: 99%